2018
DOI: 10.1002/hep4.1183
|View full text |Cite
|
Sign up to set email alerts
|

Patatin‐like phospholipase domain containing 3 variants differentially impact metabolic traits in individuals at high risk for cardiovascular events

Abstract: Single nucleotide polymorphism (SNP) rs738409 C>G in the patatin‐like phospholipase domain containing 3 (PNPLA3) gene results in an amino acid exchange from isoleucin to methionine at position I148M of PNPLA3. The expression of this loss‐of‐function mutation leads to impaired hepatocellular triglyceride hydrolysis and is associated with the development of liver steatosis, fibrosis, and hepatocellular carcinoma. In contrast to these well‐established associations, the relationship of the PNPLA3 rs738409 variant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 32 publications
(64 reference statements)
0
16
0
Order By: Relevance
“…(33) It was also shown that subsequent altered triglyceride turnover is mediated by I148M variant's sequestration of an essential cofactor for adipose triglyceride lipase activity, hence leading to HS. (34) The I148M variant appears to increase NAFLD risk through changes in lipid droplet biology within hepatocytes and hepatic stellate cells. (33,34) Interestingly, in our analyses, neither the PNPLA3 148M nor rs2281135-A allele was associated with metabolic factors, including WHR, diabetes, total and HDL cholesterol, and triglycerides.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…(33) It was also shown that subsequent altered triglyceride turnover is mediated by I148M variant's sequestration of an essential cofactor for adipose triglyceride lipase activity, hence leading to HS. (34) The I148M variant appears to increase NAFLD risk through changes in lipid droplet biology within hepatocytes and hepatic stellate cells. (33,34) Interestingly, in our analyses, neither the PNPLA3 148M nor rs2281135-A allele was associated with metabolic factors, including WHR, diabetes, total and HDL cholesterol, and triglycerides.…”
Section: Discussionmentioning
confidence: 99%
“…(34) The I148M variant appears to increase NAFLD risk through changes in lipid droplet biology within hepatocytes and hepatic stellate cells. (33,34) Interestingly, in our analyses, neither the PNPLA3 148M nor rs2281135-A allele was associated with metabolic factors, including WHR, diabetes, total and HDL cholesterol, and triglycerides. This is consistent with published reports that 148M was not associated with metabolic changes in a study of over 100 metabolic measures.…”
Section: Discussionmentioning
confidence: 99%
“…Given the impact of these variants on hepatic lipid metabolism, their modulatory role in CVD risk has also been investigated. The PNPLA3 [ [34] , [35] , [36] ] and TM6SF2 [ 34 , [36] , [37] , [38] ] NAFLD risk variants are associated with a lower-risk lipoprotein profile characterized by lower plasma TG and/or LDL-C levels. Interestingly, the effect size of the TM6SF2 E167K variant on plasma TG levels is comparable to that of a lipoprotein lipase (LPL) activating variant [ 34 ].…”
Section: Epidemiologymentioning
confidence: 99%
“…This may relate to reduced levels of circulating triglycerides (Tang et al, 2015). A recent prospective study of patients undergoing elective coronary angiography found that while there was a non-significant trend for a protective effect of the presence of PNPLA3 I148M and CAD >75% stenosis, when corrected for age, sex, use of statins, and serum highdensity lipoprotein, there was a significant protective effect (OR: 0.21, 95% CI 0.05-0.88, p = 0.03) (Rüschenbaum et al, 2018). Mendelian randomization has been used to assess the association of PNPLA3 I148M with ischemic heart disease (IHD), and although the risk of IHD increases with increased hepatic fat content, for which PNPLA3 I148M is a risk factor, there was no association with IHD (OR per M allele = 0.98, 95% CI 0.95-1.02, p = 0.79) (Lauridsen et al, 2018).…”
Section: Genetic Associations Not Discovered Through Genome Wide Assomentioning
confidence: 99%